2016
DOI: 10.1016/j.jcin.2015.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Left Main Stenting in Comparison With Surgical Revascularization

Abstract: In patients with unprotected left main coronary artery stenosis with low and medium complexity of coexisting coronary artery disease, stenting offers numerically, but statistically nonsignificant, favorable long-term outcome up to 10 years in terms of safety and efficacy outcome measures, therefore, constitutes an alternative therapy for CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…Interestingly, we observed that rates of 30-day MACCE reported in three RCTs 6,13,15 were 45% lower in PCI arm (RR 0.55, 95% CI 0.39–0.76). This was mainly driven by lower rates of stroke in the PCI arm when compared with CABG arm (RR 0.41, 95% CI 0.17–0.98) (Figure 4, Panel A ).…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…Interestingly, we observed that rates of 30-day MACCE reported in three RCTs 6,13,15 were 45% lower in PCI arm (RR 0.55, 95% CI 0.39–0.76). This was mainly driven by lower rates of stroke in the PCI arm when compared with CABG arm (RR 0.41, 95% CI 0.17–0.98) (Figure 4, Panel A ).…”
Section: Resultsmentioning
confidence: 74%
“…We identified six RCTs 5,6,10,1315 (Figure 1) enrolling 4700 patients with LMD to study the role of PCI vs. CABG. All studies had at least 1 year of follow-up, with a range of 1 to 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations